Sampling and concentration of polycyclic aromatic hydrocarbons from exhaust gases from a plant for synthesis of carbon nanomaterials - Leschev, Sergei M.; Henarava, Tatsiana M. (Journal of the Belarusian State University. Chemistry, 2021)
Currently, there is an increase in the production of carbon nanomaterials in the world, which is associated with their unique physical and mechanical properties and their use in various fields of science, industry and technology. Investigation of the chemical composition of waste gases from a propane-butane mixture pyrolysis unit during the synthesis of carbon nanomaterials is of scientific and applied value, since it allows one to study both the chemistry of the pyrolysis process of hydrocarbon mixtures and determine the degree of toxicity of waste gas from pyrolysis units. The quantitative determination of polycyclic aromatic hydrocarbons in the gaseous products of pyrolysis of a propane-butane mixture during the synthesis of carbon nanomaterials has shown that when sampling with a small amount of the Supelpak-2 adsorbent, which is widely used in international and domestic methods, efficient capture of multinuclear aromatic hydrocarbons is not ensured. Therefore, an important research issue is the development of a simple and effective method for sampling polycyclic aromatic hydrocarbons with their subsequent GC-MS analysis. The principal essence of the technique is the impregnation of two fiberglass filters with an organic low-volatile solvent – diethylene glycol, tetraethylene glycol or dimethyl sulfoxide. The latter is characterised by the highest extracting power in relation to polycyclic aromatic hydrocarbons. The developed technique makes it possible to increase the efficiency of capturing multinuclear aromatic hydrocarbons (with four or more rings in a molecule) to 96–98 % compared to a solid adsorbent under equal conditions (pyrolysis conditions, weight of adsorbent equal with filters impregnated with a solvent), where the degree of their extraction is 1–5 %. The established values of the degree of recovery of the measured components are explained by the high extracting ability of dimethyl sulfoxide in relation to multinuclear aromatic hydrocarbons.